(De-)Criminalization: introduction to the Special Issue = (Ent-)Kriminalisierung : Einleitung zum Special Issue - Negnal, Dörte (Kriminologie - das Online-Journal, 2025)
This special issue contains papers presented at the Criminology in North Rhine-Westphalia network’s annual conference on "(De-)Criminalisation", held in Siegen on March 21 and 22, 2024.